HPLC determination of lawsone in alkaline extracts of henna leaves (lawsonia inermis)/ Nurul Fasihah Idaham - Idaham, Nurul Fasihah (2010)
Due to the needs for more colouring component of natural resources component in keeping up the environment friendly, an interest was stimulated to extract of lawsone (2-hydroxy-l, 4-naphthaquinone) in alkaline medium. This study was conducted using different alkaline solvents with different values of pH which were 1.0 M NaOH, 1.0 M NaOH 0.1 M Na2C03, 1.0 M Na2C03 as well as deionised water as a blank. The presence of lawsone was identified using High Performance Liquid Chromatography (HPLC) coupled with diode array detector (DAD). The most suitable chromatographic conditions were mobile phase of water to acetonitrile with the ratio of 60:40 (% v/v), flow rate of 1.2 mL/min, 30°C as the column temperature and detection at Xmax= 260 nm. It was found that the actual amount of lawsone in the samples fall in the range of 3500 to 5500 ppm and samples of henna in 1.0 M Na2C03 yields the largest amount of lawsone (5359.96 ppm) among the other sample extracts. Thus, 1.0 M Na2C03 is the most suitable alkaline solvent that can be used in extracting large concentration of lawsone without being harmful to the environment.